Understanding the role of the advocates general in the EU judicial system - Lukić Maja (Zbornik Radova Pravnog Fakulteta u Nišu, 2016)
This paper considers primarily the role of the Advocates General of the Court of Justice of the European Union (CJEU) in the post-Lisbon Treaty environment. That role has so far evolved alongside with the evolution of the CJEU itself. After providing a brief historical overview, the author focuses on the appointment of Advocates General and the composition of their cabinets, and discusses the relevance of the Advocates General in the post-Lisbon judicial architecture of the EU. The latter assumes consideration of the ongoing transformation of the EU judicial system. The second focal point of this paper is a discussion on the question whether Advocates General are still needed, and whether they shall be needed in view of the challenges the CJEU may reasonably be expected to face in the future. The reflection comprises arguments in favor and against keeping the institute of Advocates General within the CJEU structure. Upon balancing the provided arguments, it can be concluded that the mechanism of Advocates General is indispensable to the EU since its ongoing transformation requires constant creation of legal rules. The practice so far has proved the great value of Advocates General for that particular need.